A qualitative study of healthcare providers' attitudes toward assisted partner notification for people with HIV in Indonesia - Judith A. Levy; Valerie A. Earnshaw; Ariesta Milanti; Agung Waluyo; Gabriel J. Culbert (BMC, 2023)
Abstract Background Assisted partner notification (APN) is recommended as a public health strategy to increase HIV testing in people exposed to HIV. Yet its adoption in many countries remains at an early stage. This qualitative study sought the opinions of HIV health service providers regarding the appropriateness and feasibility of implementing APN in Indonesia where such services are on the cusp of adoption. Methods Four focus group discussions totaling 40 health service providers were held in Jakarta, Indonesia to consider APN as an innovative concept and to share their reactions regarding its potential implementation in Indonesia. Voice-recorded discussions were conducted in Bahasa, transcribed verbatim, and analyzed. Results Participants recognized APN's potential in contacting and informing the partners of HIV-positive clients of possible viral exposure. They also perceived APN's value as a client-driven service permitting clients to select which of three partner notification methods would work best for them across differing partner relationships and settings. Nonetheless, participants also identified personal and health system challenges that could impede successful APN adoption including medical and human resource limitations, the need for specialized APN training, ethical and equity considerations, and lack of sufficient clarity concerning laws and government policies regulating 3rd party disclosures. They also pointed to the job-overload, stress, personal discomfort, and the ethical uncertainty that providers might experience in delivering APN. Conclusion Overall, providers of HIV services embraced the concept of APN but forecast practical difficulties in key service areas where investments in resources and system change appeared necessary to ensure effective and equitable implementation.